Properties, Morphology and Bioproduction of Bacterial Cellulose Using Static Fermentation - Roushdy, M. M. (Journal of Composites and Biodegradable Polymers, 2015)
Overview: Cellulose is the world’s major polymer of economic importance. It is the main component of wood and cotton. Cotton and wood are the major sources for most of cellulose products i.e. textiles, paper and construction compounds. Aim of Study: The work is aimed to study the probability of underutilized Hestrin-Schramm (HS) medium for the production and optimization of bacterial cellulose (BC) by Gluconacetobacter xylinus RO-7 and to study the properties of the resulted BC polymer. Methods and Results: Experiments were designed to enhance the bacterial cellulose yields along with environmental growth factors. Production of bacterial cellulose using static fermentation process was studied in HS medium at 30°C in 250 Erlenmeyer flasks by using Gluconacetobacter xylinus RO-7 isolated from local pickles markets. Results revealed that Gluconacetobacter xylinus RO-7 produced a bacterial cellulose yield of 18 gm/L. Several factors were test to increase the productivity of BC. Cellulose fibrils were subjected to thermal gravimetric, X-ray diffraction, FTIR analysis. Morphological characters of cellulose fibrils were also observed using Scanning electron microscopy. Conclusion: Microbial cellulose has many applications as scientific and biomedical endeavors. Therefore it is concluded to use the biological methods for the production of BC.